FOOD SECURITY RESEARCH MAPPING IN BARRU DISTRICT: A BIBLIOMETRIC ANALYSIS FOR FORMULATION OF REGIONAL FOOD SECURITY GUIDELINES - A.Aminah; Hj. Aidah .S (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal